Socio-Economic Correlates of Livelihood Security of Small Farmers in Jabalpur District of Madhya Pradesh - Pradhan, Sabyasachi; Naberia, Seema; Harikrishna, Yeragorla Venkata; allaraph, Venkteshwar J (Indian Journal of Extension Education, 2025)
The research study was conducted during the year 2019 to analyze the socio-economicÂ profile of the small farmers and their relationship with livelihood security in Shahpura block of district Jabalpur. Regarding relationship of respondentâ€™s profile with their livelihoodÂ security showed that education, landholding, annual income, innovativeness, extension contact, social participation, mass media exposure, economic orientation and risk orientationÂ found to have a positive and significant correlation with livelihood security of respondents. Farming experience was found to be positive and non-significant relationship with theÂ livelihood security of small farmers. Age and family type had negative and significant correlation with the livelihood security of respondents, while the family size was negativeÂ and non-significantly correlated with the livelihood security of small farmers.